Meningkatkan Kemampuan Berpikir Kritis dan Pemecahan Masalah Menggunakan Model PBL pada Kelas VII SMPN 10 Ruteng Manggarai - Maria Fatima Sarina (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve students' critical thinking and problem-solving skills through the application of the Problem-Based Learning (PBL) model on the material of Jesus the Forgiver in class VII of SMPN 10 Ruteng, Manggarai. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages.The subjects of this study were 25 students in grade VII. Data were collected through observation, tests, and interviews. The results showed that the application of the PBL model can improve students' critical thinking and problem-solving skills. This is indicated by the increase in the average student scores in each cycle and their activeness in the learning process.Thus, the application of the PBL model to the material of Jesus the Forgiver has proven effective in improving the quality of learning, especially in the aspects of critical thinking and problem solving. Therefore, it is recommended that teachers apply problem-based learning models more often in the teaching process to improve the quality of students' understanding and thinking skills.